How sensitive is a vineyard crop model to the uncertainty of its runoff module?. (November 2017) - Roux, Sébastien
Abstract: Many crop models use the NRCS Curve Number method to estimate runoff, but the simplified assumptions of this method are rarely considered in model uncertainty assessments. The associated uncertainty may be high for cropping systems with a significant part of bare soil like vineyards, specifically under a Mediterranean climate. In this work, we evaluate for a vineyard crop model the structure uncertainty coming from its uncertain runoff module. We introduce a new method based on additional knowledge about the runoff process and on a mathematical property of the model structure. Situations characterized in terms of soil water content and mean runoff conditions are studied for two applications of the vineyard model and guidelines for model users are derived. This work shows that uncertainty quantification can benefit from the knowledge of mathematical properties of a model and provide clear guidelines to model users. Highlights: We study the uncertainty of a crop model coming from its uncertain runoff module. The monotony of the model allows the uncertainty to be computed. Conditions leading to low uncertainty are obtained. Mathematical properties of a model can help studying its structure uncertainty.